The Language of Christian Ethics. A Definition of Ethical Notions as Illustrated by the Concept of Tadeusz Ślipko - Karolina Rozmarynowska (Wydawnictwo Naukowe Uniwersytetu Kardynała Stefana Wyszyńskiego w Warszawie, 2021)
The reflection that accompanies Christian ethics is concerned with its meaning and originality as seen against the background of various interpretations of morality. It usually includes questions about the characteristic subject matter of its inquiries, assumptions, methods, or inspirations. From the point of view of the considerations undertaken in this article, such reflection should also include the language employed by Christian ethics. In particular, this paper considers the following issues: (1) whether Christian ethics has its specific language; (2) whether it introduces new notions, or assigns specific meanings to notions already present in ethics; and (3) how ethical notions are defined in Christian ethics. These questions are addressed with reference to the philosophical system of Tadeusz Ślipko, one of the most outstanding Polish representatives of Christian ethics.